2002
DOI: 10.1081/ddc-120015362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fatty Acid Diesters on Permeation of Anti-Inflammatory Drugs Through Rat Skin

Abstract: Four fatty acid diesters (diethyl succinate, diethyl adipate, diethyl sebacate, and diisopropyl adipate) were used to study their enhancement effect on the permeation of four non-steroidal anti-inflammatory drugs (NSAIDs: ketoprofen, indomethacin, diclofenac sodium, and ibuprofen) through rat abdominal skin. With the diester pretreatment, drug permeation increased and the lag times decreased. No relationship was observed between the solubilities of the drugs in the diesters and the diester enhancement effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 29 publications
1
39
0
1
Order By: Relevance
“…It has previously been reported that isopropyl myristate has a fluidizing effect on the intercellular lipids of the stratum corneum 30) and that diethyl sebacate can be used to extract lipids, 17) indicating that both of these esters serve as transdermal absorption enhancers. It has also been found that ketoprofen exhibited increased permeation through hairless rat skin when it was dissolved in low MW esters, 16) and the permeability of stearyl glycyrrhetinate through Yucatan micropig skin with a finite dose was affected by the surface tension and MW of the vehicle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been reported that isopropyl myristate has a fluidizing effect on the intercellular lipids of the stratum corneum 30) and that diethyl sebacate can be used to extract lipids, 17) indicating that both of these esters serve as transdermal absorption enhancers. It has also been found that ketoprofen exhibited increased permeation through hairless rat skin when it was dissolved in low MW esters, 16) and the permeability of stearyl glycyrrhetinate through Yucatan micropig skin with a finite dose was affected by the surface tension and MW of the vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of fatty acid esters on the skin permeation of indomethacin and ketoprofen and the effect of diesters on the skin permeation of non-steroidal anti-inflammatory drugs has been reported. [15][16][17] In addition, previous studies found that the permeability of haloperidol was affected by the wettability and surface tension of the formulation.18) Furthermore, the penetration of stearyl glycyrrhetinate through Yucatan micropig skin at a finite dose was affected by the molecular weight and surface tension of the vehicles, 19) and skin permeation of model compounds through porcine skin was affected by the viscosities of the vehicles. 20) These physical properties could be a key parameter to enhance the skin permeation of chemicals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many reviews have shown that fermentative production of succinic acid can be more cost-effective than petroleumbased production schemes. [1][2][3] This type of "green" technology is becoming more popular as a means of decreasing pollution caused by many petrochemical processes. Dialkyl esters of succinic acid are widely used in detergents, cosmetics, pharmaceuticals, and processed foods.…”
Section: Introductionmentioning
confidence: 99%
“…Dialkyl esters of succinic acid are widely used in detergents, cosmetics, pharmaceuticals, and processed foods. [1][2][3] For example, dialkyl ester derivatives of diacids including succinic acid make excellent lubricants and can enhance the quality of diesel fuel when used as additives. [4][5][6] Similar approaches using fatty acid derivatives, commonly known as biodiesel, have recently been reported.…”
Section: Introductionmentioning
confidence: 99%